Cooperação e inovação na rede de empresas de software de Londrina - Tsujiguchi, Fernanda Yumi (2007)
The research analyzes the impacts of cooperation actions oriented to the improvement of the productive and innovative activity in the competitive dynamic of the software net's companies of Londrina. The analyze started identifying the actions of cooperation exists in the software companies, verifying partners, strategic alliances and contracts of cooperation and subcontracting relations between companies of the net and other agents. Characterize the collective learning process for productive and innovative capacity and identify the innovations iintroduced by the sample and the impacts relative of the learning and the innovation. The economic impacts of the cooperation actions are obtained through subjective measures of invoicing growth, net profit and return of the investment of cooperated projects. The research is characterized like quantitative, descriptive and explicative involving 26 companies of software of Londrina. The instrument of date collect follows the Redesist (2003) questionnaire composed of ordinal scales in which is possible to indicate the intensity, formalization and the localization that occur the relations of cooperation. The main results appointed: i) mayor number of partners, strategic alliances and contracts of cooperation and relations of sub contraction between companies in Londrina city to produce and commercialize softwares; ii) the R&D and/or production area and clients are the main fonts of information to the increment of innovative and productive activity; iii) the companies present high level of innovation introduction, but restricted to the indoor market; and vi) there is indication of positive result like invoicing growth, net profit and return of the investment of cooperated projects. Verified that the software net's companies of Londrina is more oriented to cooperate for producing and commercialize products and services.